Estimation of Energy Content in Drilling Wastes of Hydrocarbon Industry in India with Possibility of Utilizing This Energy - Sharma, Kavita; Gadgil, Kasturi (Asian Journal of Chemistry, 2010)
Oil and gas exploration activities have grown substantially in last few years and with higher energy demands would grow further. This process generates drilling wastes comprising of drilling fluid or mud associated with broken drill bits and grinds. A large quantity of waste is generated which is contaminated with oil and other chemicals. The present study is directed towards the estimation of energy content of this waste with possibility of utilizing this energy and simultaneously reducing the volume for safe and environment friendly disposal.